2022
DOI: 10.1021/acsestengg.2c00117
|View full text |Cite
|
Sign up to set email alerts
|

Untapped Potential: Applying Microbubble and Nanobubble Technology in Water and Wastewater Treatment and Ecological Restoration

Abstract: Microbubbles (MBs) and nanobubbles (NBs) refer to bubbles of micrometer to nanometer sizes. Due to several unique attributes, including long-term stability, negative surface charge, and the ability to generate reactive oxygen species, MB and NB technology has garnered significant attention in water and wastewater treatment and ecological restoration. Recently, several studies have shown the beneficial effects of MBs and NBs in membrane defouling, pathogen deactivation, environmental remediation, etc. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 206 publications
0
17
0
Order By: Relevance
“…19,20 In recent years, micronano-bubbles (MNBs, with diameters < 100 μm) have attracted significant attention owing to their unique physicochemical properties. 21 MNBs have large specific surface areas and excellent gas dissolution capabilities owing to their high internal pressure, acting as "gas banks" for the supplementation of more gases, such as oxygen or ozone, to aqueous solutions. In addition, previous studies have reported that numerous • OH are produced during the collapse of MNBs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…19,20 In recent years, micronano-bubbles (MNBs, with diameters < 100 μm) have attracted significant attention owing to their unique physicochemical properties. 21 MNBs have large specific surface areas and excellent gas dissolution capabilities owing to their high internal pressure, acting as "gas banks" for the supplementation of more gases, such as oxygen or ozone, to aqueous solutions. In addition, previous studies have reported that numerous • OH are produced during the collapse of MNBs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The zeta potential in the final residence time of 300 min is reported to be −21.08 ± 0.35 mV with the corresponding distribution is depicted in Figure 6B. The negative value here is assigned to the generated ROS at the bubble interface, which leads to the bubble stability (Ushikubo et al, 2010;Selihin and Tay, 2022;Zhou et al, 2022). Typically, zeta potential value can be associated to the charge of the bubble rather than its density in the water.…”
Section: Figurementioning
confidence: 96%
“…Additionally, due to surface charge (−40 to −25 mV under neutral condition) and resulting electrostatic repulsion, NBs do not readily coalesce to form larger bubbles. Consequently, NBs can remain as stable suspension in water for months . Large interfacial area per unit gas volume also enables high mass-transfer efficiencies, which are advantageous for water treatment processes , such as bioremediation (e.g., activated sludge treatment), dissolved air floatation, adsorption (i.e., enhanced interaction between the target substances and charged surface of NBs), and advanced oxidation processes (AOPs) that employ gaseous precursors such as ozone. , …”
Section: Introductionmentioning
confidence: 99%